Corporate Profitability and Stock Price Nexus: A Study of Nigeria Deposit Money Bank (NDMB) Stock Performance. - Deebii Nwiado; Silva Opuala-Charle (American Journal of Economics and Business Management, 2023)
This paper studies the relationship between the profitability of Nigeria deposit money banks (NDMB) and their stock price behaviour, noting in particular the disparity between banks’ profit and stock price. We link Banks share price to the size of total asset, return on average asset (roaa) and return on average equity (roae). Net interest margin (NIM) and of age of bank (Agb) were the other included explanatory variables. Because the study involves a subsector of the economy, we use the methodology of panel data econometric analysis that enables the inclusion of cross-sectional data of eight (8) deposit money banks over a period of 11 years. Though our finding shows a strong positive relationship between bank total assets, average return on asset and stock price, we are of the opinion such relationship is not obtainable. Nigeria deposit money bank profit has other explanations: investments in illicit unconventional banking activities, financing of illicit drug trades, investments in gas and oil etc. our conclusion is that these obtrude banks’ profits from the purview of capital market participants, thus are not anticipated by bank stock traders. These distortions do not allow bank profit to ignite market expectations, which naturally should snowball into market sentiments and eventually bank stock rally in the market.